Locally restricted glucose availability in the embryonic hypocotyl determines seed germination under abscisic acid treatment - Xue, Xueyi; Yu, Ya-Chi; Wu, Yue; Xue, Huiling; Chen, Li-Qing (The New phytologist, 2021)
• Abiotic stresses affect plant growth and development by causing cellular damage and/or restricting resources. Plants often respond to stresses through abscisic acid (ABA) signaling. Exogenous ABA application can therefore be used to mimic stress responses, which can be overridden by glucose (Glc) addition during seed germination. It remains unclear whether ABA-mediated germination inhibition is due to regional or global suppression of Glc availability in germinating Arabidopsis seeds. • We used a genetically engineered F€orster resonance energy transfer (FRET) sensor to ascertain whether ABA affects the spatiotemporal distribution of Glc, 14C-Glc uptake assays to track potential effects of ABA on sugar import, and transcriptome and mutant analyses to identify genes associated with Glc availability that are involved in ABA-inhibited seed germination. • Abscisic acid limits Glc in the hypocotyl largely by suppressing sugar allocation as well as altering sugar metabolism. Mutant plants carrying loss-of-function ABA-inducible sucrosephosphate synthase (SPS) genes accumulated more Glc, leading to ABA-insensitive germination. We reveal that Glc antagonizes ABA by globally counteracting the ABA influence at the transcript level, including expansin (EXP) family genes suppressed by ABA. • This study presents a new perspective on how ABA affects Glc distribution, which likely reflects what occurs when seeds are subjected to abiotic stresses such as drought and salt stress.